Przemiany osadnicze w neolicie i początkach epoki brązu w dorzeczu górnej i środkowej Obry. Geografia osadnictwa - Szydłowski, Marcin (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2011)
The middle and upper Obra river basin is an environmentally unique area. This large area, located in the vicinity of black soil sheets, is characterized by very favorable conditions for human occupation. The first Neolithic settlements are related to the Linear Band Pottery culture. The most commonly represented Neolithic societies belong to the Funnel Beaker Culture. During the Late Neolithic, the area was less intensively occupied. This process may be related to climate changes. The Early Bronze Age was represented in the middle Obra river basin by the Kościan group of the Unetice culture – a local community with the barrow cemetery in Łęki Małe and the fortified settlement in Bruszczewo. A continuous occupation of this area from the Early Neolithic Age to the Early Bronze Age has been proved.
The settlement changes in the upper and middle Obra river basin in the Neolithic and Early Bronze Age. The settlement geography